UPAYA PERBAIKAN KUALITAS PEMBELAJARAN PADA MATA PELAJARAN IPS DENGAN MENGATASI KENAKALAN SISWA SMP NEGERI 33 MAKASSAR - Shasliani, Shasliani; Vebriani, Nurul; Azharotunnafi, Azharotunnafi; Adi, Depict Pristine (Universitas Negeri Makassar, 2025)
This study aims to determine (1) the overview of the quality of Social Studies (IPS) learning at SMP Negeri 33 Makassar, (2) the overview of student delinquency behavior at SMP Negeri 33 Makassar, and (3) the efforts made to improve the quality of IPS learning by addressing student delinquency at SMP Negeri 33 Makassar. The type of research used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. Based on the research findings, it was revealed that: (1) The overview of the quality of IPS learning at SMP Negeri 33 Makassar includes: a) from the students' behavior, it was found that positive learning attitudes are not evenly distributed across all class groups, b) from the teaching behavior of IPS teachers, not all are able to build positive learning perceptions among students or provide the educational services needed by students, c) from the school's learning system, the school has a mission that is almost entirely achieved, and in handling student delinquency, the school has a strict violation point system implemented in collaboration with the Guidance and Counseling (BK) department and subject teachers, including IPS teachers. (2) The overview of student delinquency behavior at SMP Negeri 33 Makassar includes skipping school, damaging school aesthetics, misusing mobile phones, provoking teachers' anger, fighting, using inappropriate language, stealing, consuming drug-like substances, and inhaling glue. (3) Efforts to improve the quality of IPS learning in addressing student delinquency at SMP Negeri 33 Makassar have been carried out by the school, specifically by the BK teachers and vice-principals, through preventive, repressive, and curative measures. IPS teachers also approach students both generally and individually